EVALUASI KETERKAITAN KURIKULUM SEKOLAH MENENGAH KEJURUAN DENGAN KEBUTUHAN DUNIA KERJA DI SEKTOR INDUSTRI - Firman Firman; Argitha Jessica Putri (De Fermat : Jurnal Pendidikan Matematika, 2026)
Vocational High Schools (SMK) serve as a vital foundation in generating a prepared workforce equipped with specialized skills that align with industry requirements. SMKs should produce graduates who can utilize their skills in professional environments; thus, it is crucial to align the SMK curriculum with industry requirements to establish a connection between the education sector and the labor market. Nonetheless, in reality, the correspondence between the SMK curriculum and the actual demands of the industrial sector continues to be a complicated matter. A key reason for this gap is the insufficient participation of the industry in creating and designing the curriculum. An inflexible and top-down curriculum frequently fails to adapt to the fast-changing dynamics and shifting demands of industry, especially during the Fourth Industrial Revolution. The SMK curriculum needs to equip graduates to meet the demands of the job market, especially in the industrial field. Nonetheless, numerous graduates are considered unready for employment because of a disconnect between the curriculum material and the requirements of the industry. The objective of this research is to assess how well the vocational school curriculum corresponds with labour market demands and to determine the factors leading to this discrepancy. The approach employed involved a review of literature from different sources and policy reports. The method used for analysis was content analysis, with the data examined through multiple stages: (1) gathering literature, (2) selecting sources based on relevance and reliability, (3) data condensing, (4) categorising themes, and (5) forming conclusions. The study's findings reveal that industry participation in curriculum development is limited, the curriculum inadequately adapts to technological advancements, and the incorporation of soft skills is lacking. Enhanced cooperation between vocational institutions and the industrial sector is necessary to guarantee graduates are better equipped and more applicable.